The time of Jacob's trouble [large type] - VanLiere, Donna, 1966- (Center Point Large Print, 2020)
"A typical day at the rehabilitation center turns into a nightmare for Emma Grady when her favorite physical therapy patient vanishes in front of her, along with several colleagues. Fear turns to chaos as Emma begins the frantic race from Brooklyn to Queens, anxious to discover if her boyfriend is safe. Subways are closed, graves are open, and countless people have inexplicably disappeared. Mayhem erupts as terror grips the residents of New York City. Was this a terrorist attack? An alien abduction? Or has evil been unleashed? What else could make so many vanish in a moment? And not just in New York, but all over the globe. With so many people missing, Emma wonders if this is the predicted end of the world and begins a desperate search to discover the answers"--Provided by publisher.